Preliminary study of mangosteen nanoparticles in the sunscreen cosmeceutical product - Setyowati, Hanny; Setyani, Wahyuning (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
The growing interest in the cosmeceuticals by natural products has fostered research on the screening of plant-derived raw materials for identifying new antioxidants. Fruit peels as sources of powerful natural antioxidants are often the waste parts of various fruits from daily consumption or food industry. Among the fruit peels, mangosteen peel is an essential source of natural phenolic antioxidants. The a-mangosteen, known as the first compound of Garcinia mangostana L, has the most potent antioxidant activity among the other substances. The new application into sunscreen product will be potentially based on their activity to inhibit the photo-damaged caused by free radical elements from ultraviolet A and B (UVA and UVB). Thus, this formulation into a nanoparticle product may achieve a better effect and efficacy both as cosmetics and pharmaceutics.